Polarity of Water Transport across Epidermal Cell Membranes in Tradescantia virginiana . Issue 4 (4th February 2014) - Wada, Hiroshi; Fei, Jiong; Knipfer, Thorsten; Matthews, Mark A.; Gambetta, Greg; Shackel, Kenneth
Abstract : An outward bias polarizing of water transport, which appears to be a property of the intact membrane/protein complex of epidermal cells in situ . Abstract: Using the automated cell pressure probe, small and highly reproducible hydrostatic pressure clamp (PC ) and pressure relaxation (PR ) tests (typically, applied step change in pressure = 0.02 MPa and overall change in volume = 30 pL, respectively) were applied to individual Tradescantia virginiana epidermal cells to determine both exosmotic and endosmotic hydraulic conductivity ( L  p   OUT and L  p   IN, respectively). Within-cell reproducibility of measured hydraulic parameters depended on the method used, with the PR method giving a lower average coefficient of variation (15.2%, 5.8%, and 19.0% for half-time, cell volume [ V  o ], and hydraulic conductivity [ L  p ], respectively) than the PC method (25.4%, 22.0%, and 24.2%, respectively). V  o as determined from PC and PR tests was 1.1 to 2.7 nL and in the range of optically estimated V  o values of 1.5 to 4.9 nL. For the same cell, V  o and L  p estimates were significantly lower (about 15% and 30%, respectively) when determined by PC compared with PR . Both methods, however, showed significantly higher L  p   OUT than L  p   IN ( L  p   OUT / L  p   IN ≅ 1.20). Because these results were obtained using small and reversible hydrostatically driven flows in the same cell, the 20% outward biased polarity of water transport is most likely not due to artifacts associated with unstirred layers or to direct effects of externally applied osmotica on the membrane, as has been suggested in previous studies. The rapid reversibility of applied flow direction, particularly for the PR method, and the lack of a clear increase in L  p   OUT / L  p   IN over a wide range of L  p values suggest that the observed polarity is an intrinsic biophysical property of the intact membrane/protein complex.